LEGAL LIABILITY OF DIGITAL PLATFORMS FOR THE PRACTICE OF FAKE REVIEWS AND FAKE BUYERS - Aulia Tri Hapsari; Ferry Irawan Febriansyah; Yogi Prasetyo (SOSIOEDUKASI, 2026)
Fake reviews and fake buyers on e-commerce platforms are practices that have the potential to mislead consumers and undermine trust in the digital commerce system. The manipulation of the review system not only affects consumer decisions, but also creates injustice for good-faith business actors. This study aims to analyze the legal arrangements related to fake reviews and fake buyers from the perspective of consumer protection, focusing on the responsibilities of e-commerce platform operators in Indonesia. The research method used is normative legal research with a regulatory approach and a contextual approach, through a study of Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Information and Electronic Transactions. The results of the study show that positive law has not explicitly regulated the practice of fake reviews and fake buyers, so the responsibility of platforms is still limited as a provider of electronic means. Therefore, it is necessary to strengthen regulations to clarify the obligations of platforms in preventing digital fraud practices and protecting consumers.